The formation of small- to medium-sized Cenozoic basins drained by the Tagus river (Portugal and Spain). Example of sedimentary basins formed by crustal-scale folding - Ramón Vegas (Geogaceta, 2021)
The Tagus River drains several small- to medium-sized Cenozoic sedimentary basins situated within a tectonic depression flanked by two basement highs. These basins were formed during the initial stages of the Cenozoic compressive event that affected the interior of the Iberian Peninsula, a consequence of the Africa-Eurasia convergence. These basins exhibit distinct characteristics typical of compressional sedimentary basins, being flanked by thrusts and reverse faults. The mechanism of their formation can be attributed to crustal-scale folds, showcasing a notable and possibly exceptional instance of compressional sedimentary basins created through this tectonic mechanism.